2018
DOI: 10.1080/19349637.2017.1423001
|View full text |Cite
|
Sign up to set email alerts
|

A call for collaboration: Perception of religious and spiritual leaders on mental health (A Portuguese sample)

Abstract: To assess the relationship and collaborations between mental health professionals and religious and spiritual leaders, eleven representatives of ten different religious affiliations in Portugal participated in this qualitative study. Major findings reported show that, religious and spiritual leaders perceive themselves as important agents in promoting and preserving their congregants' mental health, as well as aiding their recovery processes; however this occurs without much referral to or collaboration with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Da Silva et al indicated that religion/spirituality was significantly and directly related to psychological health. Additionally, the results of a study conducted by Freire and Moleiro [30] revealed that religion/spirituality was a powerful predictor of psychological and physical health. Moreover, Chirico [31] found that religion and spirituality can improve and promote individuals' psychological and physical health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Da Silva et al indicated that religion/spirituality was significantly and directly related to psychological health. Additionally, the results of a study conducted by Freire and Moleiro [30] revealed that religion/spirituality was a powerful predictor of psychological and physical health. Moreover, Chirico [31] found that religion and spirituality can improve and promote individuals' psychological and physical health.…”
Section: Discussionmentioning
confidence: 99%
“…Da Silva et al indicated that there was a significant and direct relationship between religion/spirituality and mental health [29]. Additionally, a study conducted by Freire and Moleiro [30] revealed that religion/spirituality was a powerful predictor of psychological and physical health. Moreover, Chirico [31] found that psychological and physical health can be improved and promoted by religion and spirituality.…”
Section: Introductionmentioning
confidence: 99%